1984
DOI: 10.1007/bf01321456
|View full text |Cite
|
Sign up to set email alerts
|

The importance of assessing treatment integrity: An example in the anxiety disorders

Abstract: One purpose of this investigation was to examine the importance of assessing treatment integrity in a study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 9 publications
(6 reference statements)
0
26
0
2
Order By: Relevance
“…Treatment or intervention fidelity, also known as treatment/intervention integrity signifies the extent to which a treatment is implemented as intended (Vermilyea et al 1984;Yeaton & Sechrest, 1981). Treatment fidelity measures are crucial to psychological interventions, both to ascertain their efficacy (i.e., how well they work under 'ideal' highly controlled settings such as clinical trials) and their effectiveness (i.e., how well they work in the 'real-world').…”
Section: Introductionmentioning
confidence: 99%
“…Treatment or intervention fidelity, also known as treatment/intervention integrity signifies the extent to which a treatment is implemented as intended (Vermilyea et al 1984;Yeaton & Sechrest, 1981). Treatment fidelity measures are crucial to psychological interventions, both to ascertain their efficacy (i.e., how well they work under 'ideal' highly controlled settings such as clinical trials) and their effectiveness (i.e., how well they work in the 'real-world').…”
Section: Introductionmentioning
confidence: 99%
“…In psychotherapy outcome research, treatment integrity refers to the extent to which the intervention was implemented as intended [19]. It usually includes three determining components: treatment adherence, therapist competence and treatment differentiation [20].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it was assumed that patients received the interventions they were supposed to receive as designed [8]. Studies in the early eighties however, showed that this belief was flawed [9,10]. Recognition of the importance of establishing fidelity emerged from the difficult, if not impossible comparison of effectiveness, the growing emphasis on accountability, and the gap between research and practice [8].…”
Section: Introductionmentioning
confidence: 99%